Simultaneous Estimation Of Mefenamic Acid And Dicyclomine Hydrochloride By Rp-Hplc Method - DIPAL PRAJAPATI,; DR. HASUMATI RAJ, (International Journal of Pharma and Bio Sciences, 2012)
RP-HPLC method was developed in mobile phase containing Acetonitrile:Monobasic potassium dihydrogen phosphate (60:40,v/v) using C8 Luna (150 mm × 4.6 mm id, 5µm) at wavelength 215nm.The method was linear in the concentration range of 2-6μg/ml for DICY and 50-150μg/ml for MEF. The method was validated for linearity, accuracy and precision as per ICH guidelines. The developed and validated method was successfully used for the quantitative analysis of commercially available dosage form